The Influence of Digital Literacy and Income on the Consumptive Behavior of Generation Z in Gowa Regency with E-Commerce Usage as a Moderating Variable - Rijal, Syamsul; Mutmainna, A. Indah; Tadampali, Andi Caezar To; Arisah, Nur; Ratnah, Ratnah (Innovative: Journal Of Social Science Research, 2025)
This study aims to gain knowledge and understanding of the influence of digital literacy and income on the consumptive behavior of Generation Z in Gowa Regency, with e-commerce usage as a moderating variable. The method used in this research is quantitative research with a descriptive research type. The sample in this study consists of 100 respondents. Data analysis was conducted using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) model. The results show that digital literacy significantly influences consumptive behavior. Income significantly influences consumptive behavior. Digital literacy significantly influences e-commerce usage. Income significantly influences e-commerce usage. E-commerce usage significantly influences consumptive behavior. E-commerce usage is able to moderate the relationship between digital literacy and consumptive behavior. However, e-commerce usage does not moderate the relationship between income and consumptive behavior